Financial Feasibility Study in Bus Rapid Transit (BRT) Project Using Public-Private Partnership (PPP) Scheme (The Indonesian Journal of Business Administration, 2021)
"Urban traffic is one of the important keys to overcome traffic congestion and optimize the positive impact of urbanization as the main driving force of national economic growth. According to Bappenas data, 41% of the national GDP in 2017 came from 6 metropolitan areas. Given that there is no integrated public transportation system available, the resulting large number of trips, coupled with the continuous growth of the population, has resulted in an increasing demand for adequate public transportation facilities and infrastructure in City X. Therefore, PT. ABC's idea is to design a City X public transportation system that is integrated with the Jabodetabek transportation system through a public-private partnership (PPP) scheme. The system in question is mass transportation, namely Bus Rapid Transit (BRT), which implements regular and integrated public transportation services. The construction of the Bus Rapid Transit Project in city of X requires a capital investment fund of Rp 1.341.205.480.103. On that basis, it is necessary to test the feasibility of which financial feasibility is one of them. If the projects are economically feasible but financially unfeasible, the Government should support the project. In recognition of this need, on the basis of Presidential Decree No.38/2015, the Government supports for the PPP project in Indonesia is Availability Payment (AP). The concept of the agreement used in this project is Build-Operate-Transfer (BOT) which instructs the Investor to design, build, transfer projects to the Government at the end of the concession period. Through this research, authors analyze the feasibility of this investment plan by calculating the projected investment costs, revenues, and expenses needed during operation. The feasibility of an investment plan can be financed by using Discounted Cash Flow (DCF) parameters which are Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PP). To find out which variables affect the financial viability of a project, the authors use sensitivity analysis and scenario analysis. Moreover, Monte Carlo simulations are also carried out in this research to provide information regarding the probability of the effect of uncertainty from several selected variables.In the case of the Bus Rapid Transit Project with Availability Payment. The calculation result shown that the project is financially feasible with NPV of Rp. 198.686.310.240, IRR of 11% which is higher than the weighted average cost of capital (WACC) 9,27, and the payback period for 6,849 years. Availability Payment, Project Capital Expenditure, Loan interest rate and increase in wages are the variable that affect the feasibility of the project. According the Monte Carlo simulation result using 1000 iterations, the project has probability of 26% in making the project not feasible. The mean value of the Monte Carlo simulation result is Rp. 1,372,029 million which consider as favorable project. Using concept Value for Money BRT project with using PPP scheme provides better efficiency compared to development using a conventional scheme. Keywords: financial feasibility study, PPP, NPV, IRR, PP, WACC, sensitivity analysis, monte carlo analysis